The Influence Of Policy Intervention, Personal Factor, And Physical Environmental Factor On Pro-Environmental Behavior - Agustin Yolandari; Jahja Umar (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2017)
Pro-environmental behavior is an act to protect and minimize the negative impacts of human activities on the environment. The purpose from this study is to determine whetherthere's influence from interventions policy, attitude towards pro-environmental behavior, subjective norm, perceived behavioral control (PBC), environmental knowledge (system knowledge, action related knowledge, and knowledge effectiveness), physical environmental factors (physical family environmental factor and physical society environmental factor), gender and age on pro- environmental behavior. The samples are 201 people who lives in Depok and South Tangerang, who has implemented an intervention policy called "Community-based Waste Management" and the areas of which the intervention policy have not been applied. The sampling technique used is a non-probability sampling and the data analysis used is Multiple Regression Analysis on the level of significance at0.05. The results showed that there is a significant influence on the whole independent variable towards pro-environmental behavior (R2=40.1%). Minor hypothesis test results shows that there are 8 variables that have a significant influence on pro-environmental behavior which are interventions policy, subjective norm, perceived behavioral control (PBC), system knowledge, physical family environmental factor, age and interaction between policy intervention and action related knowledge.  Perilaku pro-lingkungan adalah perilaku yang dilakukan untuk melindungi, memperbaiki serta meminimalisir dampak negatif dari aktivitas manusia terhadap lingkungan. Tujuan dari penelitian ini adalah untuk mengetahui apakah ada pengaruh dari kebijakan intervensi, sikap terhadap perilaku pro-lingkungan, norma subjektif, Perceived Behavior Control (PBC), pengetahuan lingkungan (system knowledge, action related knowledge, knowledge effectiveness), faktor lingkungan fisik (faktor lingkungan fisik keluarga, faktor lingkungan fisik masyarakat), jenis kelamin dan usia terhadap perilaku pro-lingkungan. Sampel pada penelitian ini adalah masyarakat yang bertempat tinggal di Depok dan Tangerang Selatan yang telah diterapkan kebijakan intervensi “Pengelolaan Sampah Berbasis Masyarakat” dan daerah yang belum diterapkan, yaitu sebanyak 201 orang. Teknik pengambilan sampelyang digunakan adalah non-probability sampling. Analisis data yang digunakan dalam penelitian ini adalah Multiple Regression Analysis pada taraf signifikansi 0.05. Hasil penelitian ini menunjukkan bahwa ada pengaruh yang signifikan dari seluruh independent variable terhadap perilaku pro-lingkungan (R2=40,1%). Hasil uji hipotesis minor menunjukkan variabel yang memiliki pengaruh yang signifikan terhadap perilaku pro-lingkungan ialah kebijakan intervensi, norma subjektif, Perceived Behavior Control (PBC), system knowledge, faktor lingkungan fisik keluarga, usia dan interaksi antara kebijakan intervensi dan action related knowledge DOI: 10.15408/jp3i.v6i1.8147